Salinization of shallow groundwater in the Jiaokou Irrigation District and associated secondary environmental challenges - Zhang, Qiying; Qian, Hui; Ren, Wenhao; Xu, Panpan; Li, Weiqing; Yang, Qiaoyang; Shang, Jiatao (The Science of the total environment, 2024)
Understanding groundwater salinization of irrigation areas and related secondary environmental challenges is important for ensuring sustainable development. However, the mechanism under which groundwater salinization forms under the influence of long-term anthropogenic activities remains unclear. Therefore, this study analyzed the spatiotemporal variation in groundwater salinization and the underlying mechanism, and discussed the secondary environmental challenges in an irrigation area. The Jiaokou Irrigation District, North China, was adopted as a case study. The results showed a slight downward trend in groundwater salinity over the past two decades at a rate of 0.0229 g/L/y. Higher groundwater salinity was observed in areas with shallow groundwater depth. This correlation was mainly attributed to evaporative concentration, with secondary processes including natural weathering, depth of water-table, and fertilizer leaching. Drainage ditches may reduce groundwater salinity. Groundwater was transformed from freshwater to salt water and then to brackish water during the runoff process. The former transformation is mainly related to evaporation and fertilization. The latter transformation could be related to the inverse relationship between the distance to the Wei River and sediment permeability, with sediment permeability positively related to groundwater flow and leading to the discharge of salt into the Wei River. The secondary environmental challenges related to groundwater salinization in irrigation areas, mainly manifested in deterioration of irrigation water quality, soil salinization, and increased fluorine concentration. This study can act as a theoretical and practical reference for the development and utilization of water resources, ecological protection, and soil salinization in typical irrigation districts. Fig. 0 Graphical abstract (some pictures were sources from the Internet). [Display omitted] •Spatiotemporal variation and underly mechanisms of groundwater salinity in irrigation area were analyzed.•Groundwater was transformed from freshwater to salt water and then to brackish water during the runoff process.•Evaporation, depth of water-table, and fertilizer leaching were the leading reason for the high salinity.•Conceptual model of groundwater salinization was constructed.•The secondary environmental problems of groundwater salinization are discussed.